Ultrasound molecular imaging for differentiation of benign and malignant tumors in patients - Yan, Fei; Song, Zhuqing; Du, Meng; Klibanov, Alexander L. (Quantitative Imaging in Medicine and Surgery; Vol 8, No 11 (December 29, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
The differentiation of benign and malignant tumors is of great significance for the preliminary evaluation of biological behaviors and prognosis of tumors prior to surgery or other interventions (1). Histopathological examination of the tumor biopsy samples serves as the gold standard for confirming the degree of malignancy of tumors.